1981
DOI: 10.1148/radiology.141.2.7291577
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic evaluation of lymphocele formation after staging lymphadenectomy for prostatic carcinoma.

Abstract: A total of eight lymphoceles developed in six of 22 (27%) prospectively studied patients undergoing pelvic lymphadenectomy for prostatic carcinoma. Ultrasonic characteristics in these eight and in 14 retrospectively studied lymphoceles were evaluated. A location lateral to the urinary bladder was characteristic. The anterior surface of the fluid collections was usually within 3 cm of the anterior abdominal wall. No new lymphoceles developed after the first postoperative month; only one developed after the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 0 publications
3
20
2
1
Order By: Relevance
“…Some authors report a low rate of LC formation after RPE because pelvic LAE is often not routinely performed [19], or only clinically apparent LCs or those requiring intervention are reported [19,31,32]. A much higher LC rate ranging from 27 to 61% is found where LCs are specifically tested for using imaging techniques [33][34][35], which agrees with the results of our study. Heinzer et al [36] reported benefits of screening for pelvic LCs after RPE in a cohort study, as rapid treatment of LCs resulted in a significant reduction in thromboembolic events (6.2% vs. 2.1%, P < 0.049).…”
Section: Discussionsupporting
confidence: 90%
“…Some authors report a low rate of LC formation after RPE because pelvic LAE is often not routinely performed [19], or only clinically apparent LCs or those requiring intervention are reported [19,31,32]. A much higher LC rate ranging from 27 to 61% is found where LCs are specifically tested for using imaging techniques [33][34][35], which agrees with the results of our study. Heinzer et al [36] reported benefits of screening for pelvic LCs after RPE in a cohort study, as rapid treatment of LCs resulted in a significant reduction in thromboembolic events (6.2% vs. 2.1%, P < 0.049).…”
Section: Discussionsupporting
confidence: 90%
“…However, our rate was lower than that originally obtained when any sonographically or radiographically detected lymphocele was considered (range: 27-61%) (8,9). Despite an incidence of 21%, in the current study the overall rate of clinically significant SPL after PLA and RRP was 12%.…”
Section: Commentscontrasting
confidence: 76%
“…A careful review of the literature revealed only 3 other reported cases of delayed infected lymphocele after surgery [4][5][6] . Two of the reported cases had an infected lymphocele more than 1 year Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CT of patient 1 shows almost complete resolution of lymphocele (arrow) after 4 weeks. after surgery [5,6] . In all cases, the patients presented with chills and fever of unknown etiology.…”
Section: Discussionmentioning
confidence: 99%